Determining RUSLE P‐ and C‐factors for stone bunds and trenches in rangeland and cropland, North Ethiopia. (20th October 2017) - Taye, Gebeyehu; Vanmaercke, Matthias; Poesen, Jean; Van Wesemael, Bas; Tesfaye, Samuale; Teka, Daniel; Nyssen, Jan; Deckers, Jozef; Haregeweyn, Nigussie
Abstract: The implementation of soil and water conservation (SWC) measures in the Ethiopian Highlands is a top priority to reduce soil erosion rates. However, the effectiveness of these measures for different hillslope gradients and land use conditions remains poorly understood. This study addresses this knowledge gap by determining support practice (P) and cover‐management (C) factors of the Revised Universal Soil Loss Equation for commonly used SWC structures in semi‐arid environments. The factor values were calculated on the basis of soil loss data collected with 21 large runoff plots installed in rangeland and cropland sites. The P‐ and C‐factors were calculated following the recommended procedures. Results show P‐factors ranging from 0.32 to 0.74 for stone bunds, from 0.07 to 0.65 for trenches, and from 0.03 to 0.22 for stone bunds with trenches. Reduced storage capacities due to sediment deposition resulted in significant declines of the effectiveness of SWC structures over time. For example, the average P‐factor value for trenches increased from 0.1 in the first year after installation to 0.51 after 3 years. C‐factor values ranged from 0.23 to 0.82 in rangeland and from 0.03 to 0.35 in cropland. For rangeland, this large variability is due to vegetation cover changes caused by grazing. In cropland, C‐factors vary with crop types and tillage practices. The results of this study not only aid in modelling and quantifying the short‐term impacts of SWC structures on soil erosion rates but also highlight the importance of considering temporal variations of the effectiveness of SWC measures.